Identifying the Best Innovation Behaviour Hotel in the Balaton Region of Hungary - Petra Gyurácz-Németh; Nikolett Horn; Nóra Friedrich (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
The goal of the paper is to investigate the innovation behaviour of the hotels in the Balaton Region of Hungary and identify the best practice which is further analysed. The specific region has been chosen due to its popularity among Hungarian and foreign tourists, which is demonstrated by its second place in the number of guests and guest nights in the country. The research only considered those hotels which are members of the Hungarian Hotel and Restaurant Association and classified as three-, four- or five-star accommodation facilities. In the first stage the hotel general managers were asked to complete a questionnaire about the hotels' innovation behaviour. Then the best practice was identified and followed by an interview with the managers. There were 28 questionnaires completed, which is 52% of the hotels fitting the criteria. The results show that the definition of innovation is hard for the hotel general managers and hotels are focused on technological innovation, they do not concentrate on the environmental innovations and the most important barrier is the cost. The identified best practice hotel is Hotel Európa Fit****superior, which emphasises human resource and organisational innovation and introduces socalled 'innovation by inspiring'.
Keywords: L83; 330; innovation behaviour; hotel; best practice; Balaton Region